Implementation of the SCCrT–Augmented Reality Model to Improve Students’ Critical and Creative Thinking Skills and Science Literacy in Chemical Bonding Concepts - Rusmansyah; Parham Saadi; Hestu Anggrah; Ade Rahmawati Idris; Gusti Aulia Nasution; Puput Riadi; Vermiana Nur Utami (Jurnal Penelitian Pendidikan IPA, 2025)
The low level of science literacy and higher-order thinking skills among Indonesian students, as indicated by PISA results, necessitates more interactive and contextual learning innovations. This study aimed to examine the effectiveness of the SCCrT model assisted by Augmented Reality (AR) in improving students’ critical thinking, creative thinking, and science literacy in chemical bonding topics. This study used a quasi-experimental design with a nonequivalent control group design involving 11th-grade students at SMAN 1 Alalak and SMAN 12 Banjarmasin. The research instruments consisted of critical thinking, creative thinking, and science literacy tests. The results showed that the experimental groups achieved higher average post-test scores than the control groups across all variables. In critical thinking, the scores were higher in the experimental classes (82.85 and 83.56) than in the control classes (75.00 and 74.00). Creative thinking scores were higher in the experimental classes (81.54 and 82.4) than in the control classes (73.85 and 72.72). Similarly, scientific literacy scores were higher in the experimental classes (81.79 and 83.71) than in the control classes (74.47 and 73.44). Independent sample t-tests indicated significant differences between the experimental and control groups (p < 0.05) with Cohen’s d values exceeding 0.78, indicating a substantial effect. Student observations and responses also revealed positive engagement during SCCrT–AR learning activities. In conclusion, the AR-assisted SCCrT model is effective in enhancing students’ critical and creative thinking, as well as their science literacy, and represents a promising alternative for chemistry learning in the digital era.